Financial De-Dollarization : Is it for Real? - Levy Yeyati, Eduardo (IMF Working Papers; Working Paper ;, 2005)
De facto (unofficial) dollarization, defined as the holding by residents of assets and liabilities denominated in a foreign currency, is a policy concern in an increasing number of developing economies. This paper addresses the dollarization debate from this perspective, with the goal of setting the stage for a more detailed and focused discussion of whether de-dollarization should be a policy objective and, if so, how best to pursue this objective. We review existing theories of de facto dollarization and the extent to which they are supported by the available evidence, presents the main strategies for reform, and proposes a list of policy recommendations.